2019
DOI: 10.1016/j.ebr.2019.100339
|View full text |Cite
|
Sign up to set email alerts
|

No effect of electrical transcranial direct current stimulation adjunct treatment for epilepsia partialis continua in POLG disease

Abstract: We report a 15-year-old female with POLG-related mitochondrial disease who developed severe multifocal epilepsia partialis continua, unresponsive to standard anti seizure drug treatment and general anesthesia. Based on an earlier case report, we treated her focal seizures that affected her right upper limb with 20-min sessions of transcranial direct current stimulation (tDCS) at an intensity of 2 mA on each of five consecutive days. The cathode was placed over the left primary motor cortex, the anode over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The initial search from combined databases returned 228 articles (PubMed = 118 and Embase = 110). A total of 48, including 195 cases, met the inclusion criteria and were used for further evaluation [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The initial search from combined databases returned 228 articles (PubMed = 118 and Embase = 110). A total of 48, including 195 cases, met the inclusion criteria and were used for further evaluation [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to these findings, 3 clinical trials (Varga et al, 2011 ; Assenza et al, 2017 ; Lin et al, 2018 ) and two clinical cases (San-Juan et al, 2018 ; Marquardt et al, 2019 ) reported no effect of cathodal tDCS on IEDs and one clinical study revealed an increase of 48% in interictal epileptiform discharges after cathodal tDCS (Karvigh et al, 2017 ). Indeed, in a pediatric clinical study conducted by Varga et al ( 2011 ) in five children suffering from refractory continuous spike and waves during slow sleep, they found no reduction of spike-index and they assigned this result to the use of smaller tDCS electrodes than those usually used in conventional tDCS.…”
Section: Resultsmentioning
confidence: 98%
“…1. Therefore, 27 original studies met inclusion criteria and were included in this systematic review, comprising nine original sham-controlled trials [20][21][22][26][27][28][29][30][31] (Table 1) and 18 uncontrolled trials and case series/reports [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] (Tables 2 and 3). Overall, studies encompassed 328 people with epilepsy of whom 253 underwent active stimulation while 75 received sham intervention.…”
Section: Retrieved Papersmentioning
confidence: 99%
“…Despite different time lengths and stimulation spots, both found a remarkable reduction in seizure frequency. Lastly, POLG-related mitochondrial disease was also targeted for tDCS stimulation by Ng et al [45] and Marquardt et al [47] In the former study, temporary improvements on seizure frequency were only seen during tDCS, returning to baseline levels after stimulation. On the other hand, the latter study did not show any effects of active tDCS neither in seizure frequency nor IEDs.…”
Section: Uncontrolled Trials and Case Series/reportsmentioning
confidence: 99%